2020
DOI: 10.21203/rs.3.rs-30048/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between omentin-1 and major cardiovascular events after lower extremity endovascular revascularization in diabetic patients: a prospective cohort study

Abstract: Background: Cardiovascular complications represent the major cause of morbidity and mortality of type 2 diabetes mellitus (T2DM) patients. In particular, peripheral artery disease (PAD) represents a frequent T2DM vascular complication and a risk factor for the development of major adverse cardiovascular events (MACE). Among adipokines, omentin-1 serum levels are reduced in T2DM patients with PAD and are inversely related to disease severity.Objective: To study the relationship between omentin-1 levels, at base… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous meta-analyses demonstrated that serum omentin-1 concentration was independently and negatively associated with CAD and reduced in obese individuals (Agasthi et al, 2015;Arab et al, 2020). Researchers who performed studies on patients with type 2 diabetes mellitus suggest that decreased omentin-1 level may be an independent risk factor for arteriosclerosis and carotid plaque formation in these patients (Yoo et al, 2011;Nishimura et al, 2019;Biscetti et al, 2020). Low omentin-1 serum concentration was associated with acute coronary syndrome, stable angina and ischemic stroke (Shibata et al, 2011;Zhong et al, 2011;Yue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses demonstrated that serum omentin-1 concentration was independently and negatively associated with CAD and reduced in obese individuals (Agasthi et al, 2015;Arab et al, 2020). Researchers who performed studies on patients with type 2 diabetes mellitus suggest that decreased omentin-1 level may be an independent risk factor for arteriosclerosis and carotid plaque formation in these patients (Yoo et al, 2011;Nishimura et al, 2019;Biscetti et al, 2020). Low omentin-1 serum concentration was associated with acute coronary syndrome, stable angina and ischemic stroke (Shibata et al, 2011;Zhong et al, 2011;Yue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…All patients over 18 years of age with a diagnosis of T2DM present for a least one year, an Ankle/Brachial Index (ABI) of less than 80, lower limb stenosis greater than 50% documented by Ultrasound Color Doppler (US), category 4 or 5 of PAD in accord to Rutherford classi cation, presence of CLTI as previously de ned (17,34,35), and the need for endovascular treatment, were included in the study.…”
Section: Study Population and Clinical Assessmentmentioning
confidence: 99%
“…Lower-limb endovascular revascularization and follow-up after the procedure Lower-limb revascularization through balloon angioplasty and/or stenting were performed as previously described (17,34,35). Revascularization was considered successful if the residual stenosis of the treated arterial vessel was less than 30%.…”
Section: Study Population and Clinical Assessmentmentioning
confidence: 99%
“…They underwent also a detailed clinical examination, an ECG at rest, an ultrasound of carotid arteries and cerebral CT-scan to assess the presence of acute cerebrovascular disease, such as cerebral infarction. The diagnosis of T2DM was con rmed according to previous studies [24][25][26][27][28][29]. Blood hypertension was de ned as a systolic blood pressure ≥ 130 mmHg and a diastolic blood pressure ≥ 85 mmHg or presence of active anti-hypertensive treatment.…”
Section: Study Populationmentioning
confidence: 99%